AVASCULAR NECROSIS OF THE FEMORAL HEAD IN HIV-INFECTED PATIENTS: PRELIMINARY RESULTS FROM SURGICAL TREATMENT FOR CERAMIC-CERAMIC JOINT REPLACEMENT - Cabrita, Henrique Amorim (Rev Bras Ortop, 2015)
Objectives: To evaluate the initial functional results and early complication rate of ceramic-ceramic total hip replacements among patients living with HIV who presented osteonecrosis of the femoral head. Method: Twelve HIV–positive patients with a diagnosis of osteonecrosis of the incongruent femoral head were evaluated using clinical and laboratory criteria and the WOMAC functional scale before and after treatment with joint replacement. Results: We observed that 83.3% of the subjects were taking protease inhibitors, 75% had dyslipidemia and 66.6% had lipodystrophy syndrome. The improvement over the evolution of the WOMAC score was statistically significant at six and twelve months after the operation, in comparison with the preoperative score. We did not observe complications secondary to this procedure. Conclusion: Total hip arthroplasty with a ceramic-ceramic implant for treating avascular necrosis of the hip is an appropriate surgical option for this portion of the population. It provides a significant initial functional improvement and a low early complication rate.